2011
DOI: 10.1267/ahc.11031
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of the Water Channels AQP4 and AQP5 in the Rat Pituitary Gland

Abstract: The pituitary gland is composed of the adenohypophysis and neurohypophysis. The adenohypophysis contains endocrine cells, folliculo-stellate (FS) cells, and marginal layer cells, whereas the neurohypophysis mainly comprises axons and pituicytes. To understand the molecular nature of water transfer in the pituitary gland, we examined the immunohistochemical localization of the membrane water channels aquaporin-4 (AQP4) and AQP5 in rat tissue. Double immunofluorescence analysis of AQP4 and S100 protein, a known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…3). Matsuzaki et al have described the same structures in the normal anterior pituitary [12], but we were unable to detect them in controls or at any other time points after LPS injection in this study (data not shown). The reason for the discrepancy is unknown, but some elements that regulate the formation of cyst-like structures might exist in the healthy rat anterior pituitary gland.…”
contrasting
confidence: 61%
See 2 more Smart Citations
“…3). Matsuzaki et al have described the same structures in the normal anterior pituitary [12], but we were unable to detect them in controls or at any other time points after LPS injection in this study (data not shown). The reason for the discrepancy is unknown, but some elements that regulate the formation of cyst-like structures might exist in the healthy rat anterior pituitary gland.…”
contrasting
confidence: 61%
“…Our previous studies have shown that AQP4 protein is expressed in some FS cells and marginal layer cells in Rathke's residual pouch, but not in any hormoneproducing cells in the adenohypophysis [9,10]. Matsuzaki et al have reported similar immunohistochemical observations using their own AQP4 antibody [12]. In this study, the level of AQP4 transcripts was examined in whole anterior lobes, which included both FS cells and marginal cells, and we were therefore unable to determine whether mRNA for AQP4 had elevated in FS cells and/or marginal cells.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Paraffin sections were mounted on adhesive glass slides (Platinum; Matsunami, Osaka, Japan). For antigen retrieval, paraffin sections were placed in 20 mM Tris-HCl buffer (pH 9.0) and heated in a microwave oven (MI-77, AZUMAYA, Tokyo, Japan) for 30 min at 97°C [ 15 ]. Both frozen and paraffin sections were then incubated with 5% normal donkey serum-PBS to block non-specific binding of antibodies and subsequently incubated with anti-AQP5 polyclonal antibody (AffGPTM41, AffRaTM41, or AffRaTM14) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Membrane water channel aquaporins provide specific pathway for transcellular water transfer in water-handling organs and tissues, such as kidney and salivary glands [ 11 , 12 , 14 , 15 , 29 ]. Aquaporin-5 (AQP5), which is predominantly found in the glandular tissues, is present in the luminal surface membrane of salivary gland acinar cells and provides a transcellular water transfer pathway for salivary fluid secretion [ 10 , 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%